2015
DOI: 10.1111/mec.13409
|View full text |Cite
|
Sign up to set email alerts
|

Environmental adaptation in Chinook salmon (Oncorhynchus tshawytscha) throughout their North American range

Abstract: Landscape genomics is a rapidly growing field with recent advances in both genotyping efficiency and statistical analyses that provide insight towards local adaptation of populations under varying environmental and selective pressure. Chinook salmon (Oncorhynchus tshawytscha) are a broadly distributed Pacific salmon species, occupying a diversity of habitats throughout the northeastern Pacific with pronounced variation in environmental and climate features but little is understood regarding local adaptation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
122
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(132 citation statements)
references
References 106 publications
(150 reference statements)
10
122
0
Order By: Relevance
“…; Hecht et al . ). However, our ability to test for patterns of polygenic adaptation was limited in this study, and future work would benefit from a greater number of genetic markers and testing approaches specific to discovering polygenetic adaptation.…”
Section: Discussionmentioning
confidence: 97%
“…; Hecht et al . ). However, our ability to test for patterns of polygenic adaptation was limited in this study, and future work would benefit from a greater number of genetic markers and testing approaches specific to discovering polygenetic adaptation.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have identified SNP markers linked to migration timing in both Chinook salmon (Brieuc, Ono, Drinan, & Naish, ) and steelhead trout ( O. mykiss ; Hess, Zendt, Matala, & Narum, ). Finally, Hecht, Matala, Hess, and Narum () linked variation in RAD markers with 24 environmental correlates using redundancy analysis in Chinook salmon, finding that freshwater migration distance was the environmental variable explaining most of the genomic variation. This last result parallels our own observations suggesting the importance of migratory harshness and is also corroborated by many classic studies demonstrating the importance of migratory difficulty as a selective factor driving adaptation in morphological, physiological and life history traits (Bernatchez & Dodson, ; Crossin et al., ; Eliason et al., ; Schaffer & Elson, ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, fewer fish studies have used a landscape genomic framework to detecting selection by finding statistical associations between local allele frequencies and environmental variables and those have mainly been performed on salmonids (Zueva et al , ; Hecht et al , ; Hand et al , ). For instance, Hecht et al () used RADseq to genotype nearly 2000 Chinook salmon Oncorhynchus tshawytscha (Walbaum 1792) from 46 localities at about 20 000 SNPs in order to document environmental adaptation throughout the North American range of the species, from California to Alaska. They applied a multivariate landscape genomic technique (redundancy analysis, RDA), to identify correlations between genetic markers and 24 environmental and climatic traits.…”
Section: Modern Approaches To Study Genomics Of Local Adaptationmentioning
confidence: 99%